2021
DOI: 10.1097/spv.0000000000001095
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Obstruction After Sacrocolpopexy: A Case Series

Abstract: It is estimated that more than 30 million women in the United States are affected by pelvic floor disorders. Of these, 3 million experience pelvic organ prolapse. A robust surgical option for treatment of vaginal vault prolapse is sacrocolpopexy (SC).A rare but life-threatening possible sequela of SC is bowel obstruction. There are only limited data on its prevention, prevalence, detection, and management.Previous studies reported rates of bowel obstruction after SC ranging from 1.9% to 2.5%. A comprehensive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Bowel obstruction associated with Sacrocolpopexy was reported in two cases, in our study; one was two years after surgery, and the second was seven years after surgery. Wadensweiler et al 32 in 2021 reported an incidence of 1% average presentation time (2.5–8.8 years). Pue et al 33 said a similar delayed incidence approximately 14 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel obstruction associated with Sacrocolpopexy was reported in two cases, in our study; one was two years after surgery, and the second was seven years after surgery. Wadensweiler et al 32 in 2021 reported an incidence of 1% average presentation time (2.5–8.8 years). Pue et al 33 said a similar delayed incidence approximately 14 years after surgery.…”
Section: Discussionmentioning
confidence: 99%